Gas-liquid-solid three-phase foam stabilizer and high-strength autoclaved aerated concrete plate

The gas-liquid-solid three-phase foam stabilizer prepared by using modified layered bimetallic hydroxide nanosheets and surfactant during the foaming of aerated concrete, the poor impact resistance and low strength of aerated concrete sheets are solved. The problem of this achieves higher compressive strength and impact resistance, and is environmentally friendly.

CN119241119AActive Publication Date: 2025-01-03ANHUI CROCODILE NICA NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411444090.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-03
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing aerated concrete slabs have poor impact resistance and low strength, and traditional foam stabilizers are difficult to effectively improve their performance.

Method used

Design a gas-liquid-solid three-phase foam stabilizer to form nanometers by preparing a layered bimetal hydroxide with a high dispersion ultra-thin sheet-like structure in aqueous solution and modifying it with long alkyl chain anionic surfactant. The three-phase gas-liquid-solid foam stabilizer of the sheet structure is used to generate more uniform pore sizes and more crystal products during the foaming process of aerated concrete to improve strength.

Benefits of technology

The compressive strength and impact resistance of aerated concrete are significantly improved, and the strength of the gas-solid interface is enhanced by generating hydration products on the foam interface, and the preparation process is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a gas-liquid-solid three-phase foam stabilizer and a high-strength autoclaved aerated concrete plate, and belongs to the technical field of building material preparation, the three-phase foam stabilizer is an aqueous solution containing long alkyl chain anionic compound modified layered double hydroxides and a surfactant, the mass ratio of the long alkyl chain anionic compound modified layered double hydroxide to the surfactant is (1: 5)-(1: 10). According to the high-strength autoclaved aerated concrete plate prepared by using the three-phase foam stabilizer as the foam stabilizer, gas-liquid-solid three phases are formed after foaming, and solid nanosheets subjected to surface modification by using long-carbon-chain organic matters can exist on the surface of foam and have a crystal nucleus effect on a gas-liquid interface generated in the foaming process of the aerated concrete; a hydration product capable of improving the strength of a gas-solid interface in the aerated concrete is generated by utilizing the reaction participated on the interface, so that higher strength is provided for the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material preparation, and relates to a gas-liquid-solid three-phase foam stabilizer for preparing high-strength aerated concrete. Background Art

[0002] Autoclaved aerated concrete board is made of cement, As the main raw materials, different amounts of antiseptic treated A new type of lightweight porous Building materials. , the reaction produces autoclaved aerated concrete boards with porous crystals, which have a lower density than general cementitious materials and have unparalleled properties such as good fire resistance, fire prevention, sound insulation, heat insulation and thermal insulation. Replacing traditional aerated concrete blocks and cement slag hollow wall panels with autoclaved aerated concrete panels can not only greatly reduce engineering time, improve engineering installation quality and reduce construction costs, but also achieve the goals of protecting the environment, saving energy, improving wall surface quality, increasing building aesthetics and improving indoor environmental comfort. However, due to the porous structure of the product, the products in the industry currently generally have poor impact resistance and low compressive strength. This feature leads to a high breakage rate during the board breaking process and subsequent transportation. In order to improve the performance of the product, a foam stabilizer is usually used in the production process of aerated concrete panels, mainly to make the bubbles more uniform, reduce through holes, and make the product have a uniform pore size of suitable size, thereby increasing the mechanical strength of the aerated concrete panels to a certain extent. Traditional foam stabilizers are usually surfactants, which can improve the compressive strength and impact resistance of products to a certain extent by reducing the surface tension of bubbles, enhancing the stability of bubbles, prolonging their residence time, and ultimately making concrete have a better pore structure. However, relying solely on this type of foam stabilizer to improve the strength of products is very limited. Therefore, it is sought to design a gas-liquid-solid three-phase foam stabilizer with excellent performance, which is not only conducive to the formation of closed pores with suitable and uniform pore sizes inside the aerated concrete during the foaming process of aerated concrete, but also can generate more crystalline products on the foam interface. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and seek to design a gas-liquid-solid three-phase foam stabilizer that can not only help form closed pores with suitable and uniform pore sizes inside the aerated concrete during the foaming process of the aerated concrete, but also generate more crystalline products on the foam interface, thereby solving the problems of poor impact resistance and low strength of aerated concrete board products in the prior art.

[0004] In order to achieve the above-mentioned purpose, the gas-liquid-solid three-phase foam stabilizer involved in the present invention is an aqueous solution of a layered double hydroxide modified with a long alkyl chain anion compound and a surfactant. Calculated based on the mass of the layered double hydroxide modified with a long alkyl chain anion compound after drying, the mass ratio of the layered double hydroxide modified with a long alkyl chain anion compound to the surfactant is 1:5-1:10.

[0005] The gas-liquid-solid three-phase foam stabilizer prepared by the present invention is prepared by preparing a layered double metal hydroxide with a highly dispersed ultra-thin flaky structure in an aqueous solution, and then modifying the surface of the layered double metal hydroxide with a long-chain anionic surfactant, and then mixing the layered double metal hydroxide with a surfactant to form a gas-liquid-solid three-phase foam stabilizer. The gas-liquid-solid three-phase foam stabilizer is added to aerated concrete slurry, which can not only play a role in stabilizing foam in the process of gas generation, but also provide crystal nuclei for crystal growth, increase hydration products at the gas-solid interface in the process of steam curing, and thus improve the strength of the aerated concrete.

[0006] The preparation method of the gas-liquid-solid three-phase foam stabilizer disclosed by the present invention specifically comprises the following steps:

[0007] (1) dispersing 10-20 g of layered double hydroxide precipitate in 20 ml of 0.005-0.1 mol / l long alkyl chain anion compound solution to obtain a uniformly dispersed suspension;

[0008] (2) Mix 20 ml of the above suspension with 3-7 ml of surfactant and mix thoroughly to obtain a gas-liquid-solid three-phase foam stabilizer.

[0009] Furthermore, in step (1), the layered double hydroxide is prepared by a conventional co-precipitation method or a microchannel reactor method, preferably a microchannel reactor method.

[0010] Furthermore, the reaction temperature of the conventional co-precipitation method or the microchannel reactor method is 30-50° C., and the reaction time is 0.5-2 hours.

[0011] 10-20g of layered double hydroxide precipitate is dispersed in 20ml of 0.005-0.1mol / l long alkyl chain anion compound solution, and the ultrasonic dispersion time is 5-15 min at a temperature of 25-35 o C.

[0012] Furthermore, the general formula of the layered double hydroxide precipitate is [M 2+ 1-x M 3+ x (OH)2] x+ (A n- ) x / n ·yH2O, where M2+ For the divalent metal ion Mg 2+ , Ca 2+ 、Zn 2+ Any one or both of M 3+ For Al 3+ or Fe 3 + ; A n- NO3 - 、CO3 2- or Cl - Any one of the following; 0.17≤x≤0.35; 0≤y≤2.

[0013] Furthermore, the long alkyl chain anionic compound is C n-1 H 2n-1 XOO - M + , n=11-22, X represents chemical elements C, S, P, M + Represents monovalent metal ion K + 、Na + , specifically: sodium (potassium) laurate, sodium (potassium) stearate, sodium (potassium) palmitate.

[0014] Further, the mass ratio of the long alkyl chain anion compound to the layered double metal hydroxide is 1:5 to 1:60, calculated based on the mass of the layered double metal hydroxide after drying. Further, the mass ratio of the layered double metal hydroxide modified with the long alkyl chain anion compound to the surfactant is 1:5 to 1:10, calculated based on the mass of the layered double metal hydroxide modified with the long alkyl chain anion compound after drying.

[0015] Furthermore, the surfactant is one or more of coconut acid diethanolamide, disodium lauroylamphodiacetate, cocamidopropylamine oxide, disodium lauryl citrate sulfosuccinate, disodium lauryl ether sulfosuccinate monoester, sodium fatty alcohol polyvinyl ether carboxylate, oleic acid diethanolamide, disodium lauryl sulfosuccinate monoester, disodium coconut oil amphodiacetate, sodium lauroyl sarcosinate, and sodium lauroyl glutamate.

[0016] A method for preparing an autoclaved high-strength aerated concrete board, specifically comprising:

[0017] (1) 10 parts of washed sand, 0.8-1.2 parts of gypsum, and 9-11 parts of water are mixed and ground into slurry, and then mixed with 2-2.6 parts of cement, 1.8-2.2 parts of quicklime, 2.5-3 parts of fly ash, and 1.2-1.8 parts of water to obtain high-strength aerated concrete slurry;

[0018] (2) A certain amount of aluminum powder for foaming is dispersed in a gas-liquid-solid three-phase foam stabilizer, wherein the masses of the aluminum powder and the gas-liquid-solid three-phase foam stabilizer are 0.07-0.10% and 0.20-0.3% of the mass of the solid powder in step (1), respectively. After being evenly stirred, the mixture is directly poured into a high-strength aerated concrete slurry. The mixture is first rapidly stirred for 45 seconds in a cement slurry mixer, then slowly stirred for 30 seconds. The slurry is quickly poured into a test mold and placed in a standard constant temperature and humidity curing box at 45°C for curing. The curing is stopped for 4 hours. The test block that has been cured is demolded and sent into an autoclave at a saturated steam pressure of 1.5 MPa and a high temperature of 190°C for high temperature and high pressure curing.

[0019] Different from traditional foam stabilizers, this gas-liquid-solid three-phase foam stabilizer is mainly composed of surfactants, surface-modified nanosheets and water. After foaming, gas-liquid-solid three-phases are formed. The solid nanosheets surface-modified with long carbon chain organic matter can exist on the foam surface and act as crystal nuclei on the gas-liquid interface generated during the foaming process of aerated concrete. They participate in the reaction at the interface to generate hydration products that can improve the strength of the gas-solid interface in the aerated concrete, thereby providing higher strength for the product.

[0020] Compared with the prior art, the present invention has the following advantages: (1) the gas-liquid-solid three-phase foam stabilizer is composed of surface-modified layered double metal hydroxide nanosheets, a surfactant and water. The nanosheets have an ultra-thin sheet structure with a lateral size of 20-30 nm, which provides crystal nuclei for the hydration of aerated concrete and promotes the formation of hydration products; (2) the surface of the nanosheets is modified with anionic surfactants, which have good compatibility with the foaming agent; (3) the only solvent used in the preparation process is water, which is environmentally friendly. DETAILED DESCRIPTION

[0021] The present invention will be further described below by way of examples.

[0022] Embodiment 1:

[0023] The specific process steps of this embodiment are:

[0024] (1) Dissolve Zn(NO3)2 and Al(NO3)3 in 50 ml of deionized water to prepare a mixed salt solution with a total metal ion concentration of 0.3 mol / l; the molar ratio of Zn to Al is 2:1; prepare 50 ml of 7% ammonia solution;

[0025] (2) The mixed salt solution and the ammonia solution are mixed and reacted by using a T-type microreactor method to obtain a layered double hydroxide suspension at 25 o C and stir thoroughly for 30 min;

[0026] (3) The layered double hydroxide suspension prepared in step (2) was centrifuged and then washed with deionized water to obtain a layered double hydroxide precipitate. 10 g of the layered double hydroxide precipitate was dispersed in 20 ml of a 20 mmol / l potassium laurate solution and stirred at 30 °C for 24 h. o C for 2 hours to obtain a uniformly dispersed suspension;

[0027] (4) The product obtained in step (3) was mixed with 5 g of coconut oil methyl monoethanolamide to prepare a gas-liquid-solid three-phase foam stabilizer.

[0028] Embodiment 2:

[0029] The specific process steps of this embodiment are:

[0030] (1) Dissolve Mg(NO3)2 and Al(NO3)3 in 50 ml of deionized water to prepare a mixed salt solution with a total metal ion concentration of 0.3 mol / l; the molar ratio of Mg to Al is 2:1; prepare 50 ml of 7% ammonia solution;

[0031] (2) The mixed salt solution and the ammonia solution are mixed and reacted by using a T-type microreactor method to obtain a layered double hydroxide suspension at 25 o C and stir thoroughly for 30 min;

[0032] (3) The layered double hydroxide suspension prepared in step (2) was centrifuged and then washed with deionized water to obtain a layered double hydroxide precipitate. 10 g of the layered double hydroxide precipitate was dispersed in 20 ml of a 20 mmol / l potassium laurate solution and stirred at 30 °C for 24 h. o C for 2 hours to obtain a uniformly dispersed suspension;

[0033] (4) The product obtained in step (3) was mixed with 5 g of coconut oil diethanolamide to prepare a gas-liquid-solid three-phase foam stabilizer.

[0034] Embodiment 3:

[0035] The specific process steps of this embodiment are:

[0036] (1) Dissolve Ca(NO3)2 and Al(NO3)3 in 50 ml of deionized water to prepare a mixed salt solution with a total metal ion concentration of 0.3 mol / l; the molar ratio of Ca to Al is 2:1; prepare 50 ml of 7% ammonia solution;

[0037] (2) The mixed salt solution and the ammonia solution are mixed and reacted by using a T-type microreactor method to obtain a layered double hydroxide suspension at 25o C and stir thoroughly for 30 min;

[0038] (3) The layered double hydroxide suspension prepared in step (2) was centrifuged and then washed with deionized water to obtain a layered double hydroxide precipitate. 10 g of the layered double hydroxide precipitate was dispersed in 20 ml of a 20 mmol / l potassium laurate solution and stirred at 30 °C for 24 h. o C for 2 hours to obtain a uniformly dispersed suspension;

[0039] (4) The product obtained in step (3) was mixed with 5 g of cocamidopropylamine oxide to prepare a gas-liquid-solid three-phase foam stabilizer.

[0040] Embodiment 4:

[0041] The specific process steps of this embodiment are:

[0042] (1) Dissolve Mg(NO3)2 and Al(NO3)3 in 50 ml of deionized water to prepare a mixed salt solution with a total metal ion concentration of 0.3 mol / l; the molar ratio of Mg to Al is 2:1; prepare 50 ml of 7% ammonia solution;

[0043] (2) The mixed salt solution and the ammonia solution are mixed and reacted by using a T-type microreactor method to obtain a layered double hydroxide suspension at 25 o C and stir thoroughly for 30 min;

[0044] (3) The layered double hydroxide suspension prepared in step (2) was centrifuged and then washed with deionized water to obtain a layered double hydroxide precipitate. 10 g of the layered double hydroxide precipitate was dispersed in 20 ml of a 20 mmol / l potassium laurate solution and stirred at 30 °C for 24 h. o C for 2 hours to obtain a uniformly dispersed suspension;

[0045] (4) The product obtained in step (3) was mixed with 2.5 g of cocamidopropylamine oxide and 2.5 g of cocoyl diethanolamide to prepare a gas-liquid-solid three-phase foam stabilizer.

[0046] Embodiment 5:

[0047] The specific process steps of this embodiment are:

[0048] (1) Dissolve Mg(NO3)2 and Al(NO3)3 in 50 ml of deionized water to prepare a mixed salt solution with a total metal ion concentration of 0.3 mol / l; the molar ratio of Mg to Al is 2:1; prepare 50 ml of 7% ammonia solution;

[0049] (2) The mixed salt solution and the ammonia solution are mixed and reacted by using a T-type microreactor method to obtain a layered double hydroxide suspension at 25 o C and stir thoroughly for 30 min;

[0050] (3) The layered double hydroxide suspension prepared in step (2) was centrifuged and then washed with deionized water to obtain a layered double hydroxide precipitate. 10 g of the layered double hydroxide precipitate was dispersed in 20 ml of a 20 mmol / l potassium laurate solution and stirred at 30 °C for 24 h. o C for 2 hours to obtain a uniformly dispersed suspension;

[0051] (4) The product obtained in step (3) was mixed with 5 g of disodium lauryl ether sulfosuccinate to prepare a gas-liquid-solid three-phase foam stabilizer.

[0052] Application examples:

[0053] A method for preparing an autoclaved high-strength aerated concrete board, specifically comprising:

[0054] (1) 10 parts of washed sand, 1 part of gypsum and 10 parts of water are mixed and ground into slurry, and then mixed with 2.3 parts of cement, 2 parts of quicklime, 2.7 parts of fly ash and 1.5 parts of water to obtain high-strength aerated concrete slurry;

[0055] (2) A certain amount of aluminum powder was dispersed in the gas-liquid-solid three-phase foam stabilizer prepared in Example 1-5, wherein the mass of the aluminum powder and the gas-liquid-solid three-phase foam stabilizer was 0.08% and 0.25% of the mass of the solid powder in step (1), respectively. After being evenly stirred, the mixture was directly poured into the high-strength aerated concrete slurry. The mixture was first rapidly stirred for 45 seconds in a cement slurry mixer, then slowly stirred for 30 seconds. The slurry was quickly poured into a test mold and placed in a standard constant temperature and humidity curing box at 45°C for curing. The cured specimens were allowed to stand for 4 hours to generate gas. The cured specimens were demolded and placed in an autoclave at a saturated steam pressure of 1.5 MPa and a high temperature of 190°C for high temperature and high pressure curing. The autoclaved specimens were then taken out and tested for compressive strength. The results are shown in Table 1. It can be seen that the gas-liquid-solid three-phase foam stabilizer composed of a mixture of layered double hydroxides modified by long alkyl chain anionic compounds and surfactants can further enhance the compressive strength and impact resistance of the test block on the basis of Comparative Example 2. This is because the gas-liquid-solid three-phase foam stabilizer can increase the production of hydration products in the solid layer between bubbles, thereby improving the overall strength of the product.

[0056] Comparative Example 1:

[0057] The specific process steps of this comparative example are:

[0058] (1) Mix 10 parts of washed sand, 1 part of gypsum, and 10 parts of water and grind them into a slurry. Then mix them with 2.3 parts of ordinary Portland cement (PO.42.5), 2 parts of quicklime, 2.7 parts of fly ash, and 1.5 parts of water.

[0059] (2) A certain amount of aluminum powder is dispersed in a small amount of water, wherein the mass of the aluminum powder and the water is 0.08% and 0.25% of the mass of the solid powder in step (1), respectively. After being evenly stirred, the mixture is directly poured into the slurry prepared in step (1), first stirred rapidly for 45 seconds in a cement slurry mixer, then stirred slowly for 30 seconds, and the slurry is quickly poured into a test mold, and placed in a standard constant temperature and humidity curing box at 45°C for curing, and gasification is stopped for 4 hours; the test block after static curing is demolded, and sent to an autoclave with a saturated steam pressure of 1.5 MPa and a high temperature of 190°C for high temperature and high pressure curing, and the autoclaved high-strength aerated concrete test block after autoclaving is taken out for compressive strength testing, and the results are shown in Table 1. The autoclaved high-strength aerated concrete test block prepared in this comparative example under the action of the foaming agent aluminum powder has uneven internal bubbles to form a large number of through holes, and has low compressive strength.

[0060] Comparative Example 2:

[0061] The specific process steps of this comparative example are:

[0062] (1) Mix 10 parts of washed sand, 1 part of gypsum, and 10 parts of water and grind them into a slurry. Then mix them with 2.3 parts of ordinary Portland cement (PO.42.5), 2 parts of quicklime, 2.7 parts of fly ash, and 1.5 parts of water.

[0063] (2) A certain amount of aluminum powder is dispersed in an aqueous solution of cocamidopropylamine oxide, wherein the masses of the aluminum powder and the aqueous solution of cocamidopropylamine oxide are 0.08% and 0.25% of the mass of the solid powder in step (1), respectively, and the mass of cocamidopropylamine oxide in the aqueous solution of cocamidopropylamine oxide is 5 g. The aluminum powder liquid is uniformly stirred to obtain the aluminum powder liquid, which is then directly poured into the slurry prepared in step (1). The slurry is first rapidly stirred for 45 seconds in a cement slurry mixer, then slowly stirred for 30 seconds, and the slurry is quickly poured into a test mold, and placed in a standard constant temperature and humidity curing box at 45°C for curing, and gas is allowed to stand for 4 hours; the test block that has been cured is demolded and sent to an autoclave with a saturated steam pressure of 1.5 MPa and a high temperature of 190°C for high temperature and high pressure curing. The autoclaved test block is taken out and the compressive strength test is performed. The results are shown in Table 1. Compared with Comparative Example 1, this comparative example makes the bubbles more uniform by adding cocamidopropylamine oxide surfactant, enhances the stability of the bubbles, forms a uniform and stable pore structure, and improves the compressive strength of the product to a certain extent.

[0064] Comparative Example 3

[0065] The specific process steps of this comparative example are:

[0066] (1) Mix 10 parts of washed sand, 1 part of gypsum, and 10 parts of water and grind them into a slurry. Then mix them with 2.3 parts of ordinary Portland cement (PO.42.5), 2 parts of quicklime, 2.7 parts of fly ash, and 1.5 parts of water.

[0067] (2) Mix a certain amount of aluminum powder and 10 g A layered double hydroxide precipitate prepared from Mg(NO3)2 and Al(NO3)3 (see Example 2 for details) is dispersed in an aqueous solution of cocamidopropylamine oxide, wherein the masses of aluminum powder and cocamidopropylamine oxide aqueous solution are 0.08% and 0.25% of the mass of the solid powder in step (1), respectively, and the mass of cocamidopropylamine oxide in the aqueous solution of cocamidopropylamine oxide is 5g. The aluminum powder liquid is uniformly stirred to obtain the aluminum powder liquid, which is then directly poured into the slurry obtained in step (1), first rapidly stirred for 45s in a cement slurry mixer, then slowly stirred for 30s, and the slurry is quickly poured into a test mold, and placed in a standard constant temperature and humidity curing box at 45°C for curing, and allowed to stand for 4 hours to generate gas; the test block that has been cured is demolded and sent to an autoclave with a saturated steam pressure of 1.5MPa and a high temperature of 190°C for high temperature and high pressure curing, and the autoclaved test block is taken out and tested for compressive strength, and the results are shown in Table 1. Compared with Comparative Example 2 and Example 2, the layered double hydroxide precipitate of this comparative example does not play a significant role in terms of strength. This is because the surface of the layered double hydroxide without surface modification is hydrophilic and is more easily dispersed in water during the foaming process rather than existing on the foam surface, so it cannot promote the formation of crystalline products at the gas-solid interface during the hydration process.

[0068] Table 1

Claims

1. Gas-liquid-solid three-phase foam stabilizer, characterized in that: The invention relates to an aqueous solution containing a layered double hydroxide modified with a long alkyl chain anion compound and a surfactant. The mass ratio of the long alkyl chain anion compound to the layered double hydroxide is 1:5-1:60, calculated based on the mass of the layered double hydroxide after drying. The mass ratio of the layered double hydroxide modified with a long alkyl chain anion compound to the surfactant is 1:5-1:10, calculated based on the mass of the layered double hydroxide modified with a long alkyl chain anion compound after drying.

2. The gas-liquid-solid three-phase foam stabilizer according to claim 1, characterized in that: The surfactant is one or more of coconut acid diethanolamide, disodium lauroylamphodiacetate, cocamidopropylamine oxide, disodium lauryl citrate sulfosuccinate, disodium lauryl ether sulfosuccinate monoester, sodium fatty alcohol polyvinyl ether carboxylate, oleic acid diethanolamide, disodium lauryl sulfosuccinate monoester, disodium coconut oil amphodiacetate, sodium lauroyl sarcosinate, and sodium lauroyl glutamate.

3. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 1, characterized in that: The specific steps include: (1) dispersing 10-20 g of layered double hydroxide precipitate in 20 ml of 0.005-0.1 mol / l long alkyl chain anion compound solution to obtain a uniformly dispersed suspension; (2) Mix 20 ml of the above suspension with 3-7 ml of surfactant and mix thoroughly to obtain a gas-liquid-solid three-phase foam stabilizer.

4. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 3, characterized in that: In step (1), the layered double metal hydroxide is prepared by a conventional co-precipitation method or a microchannel reactor method.

5. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 3, characterized in that: Disperse 10-20g of layered double hydroxide precipitate in 20ml of 0.005-0.1mol / l long alkyl chain anion compound solution, ultrasonically disperse for 5-15 min at a temperature of 25-35 o C.

6. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 3, characterized in that: The general formula of the layered double hydroxide precipitate is [M 2+ 1-x M 3+ x (OH)2] x+ (A n- ) x / n ·yH2O, where M 2+ For the divalent metal ion Mg 2 + , Ca 2+ 、Zn 2+ Any one or both of M 3+ For Al 3+ or Fe 3+ ; A n- NO3 - 、CO3 2- or Cl - Any one of the following; 0.17≤x≤0.35; 0≤y≤2.

7. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 3, characterized in that: The long alkyl chain anionic compound is C n-1 H 2n-1 XOO - M + , n=11-22, X represents chemical elements C, S, P, M + Represents monovalent metal ion K + 、Na + .

8. The method for preparing the gas-liquid-solid three-phase foam stabilizer according to claim 3, characterized in that: Calculated based on the mass of the layered double metal hydroxide after drying, the mass ratio of the long alkyl chain anion compound to the layered double metal hydroxide is 1:10 to 1.5:

10.

9. An autoclaved high-strength aerated concrete board, characterized in that: The specific preparation method is: (1) 10 parts of washed sand, 0.8-1.2 parts of gypsum, and 9-11 parts of water are mixed and ground into slurry, and then mixed with 2-2.6 parts of cement, 1.8-2.2 parts of quicklime, 2.5-3 parts of fly ash, and 1.2-1.8 parts of water to obtain high-strength aerated concrete slurry; (2) A certain amount of aluminum powder for foaming is dispersed in the gas-liquid-solid three-phase foam stabilizer prepared in claim 1, wherein the masses of the aluminum powder and the gas-liquid-solid three-phase foam stabilizer are 0.07-0.10% and 0.20-0.3% of the mass of the solid powder in step (1), respectively; after being evenly stirred, the mixture is directly poured into high-strength aerated concrete slurry; the mixture is first stirred rapidly and then slowly stirred in a cement slurry mixer; the slurry is quickly poured into a test mold; and the mixture is cured in a standard constant temperature and humidity curing box to allow gas to be generated; after the test block has been cured, the mold is removed and high temperature and high pressure curing is performed.

Citation Information

Patent Citations

  • Laminar bimetal hydroxide and preparation method thereof

    CN102976278A

  • Modified mineral foaming agent for building foam concrete and preparation method thereof

    CN107512860A

  • Hydroxyl compound type composite foaming agent and preparation method thereof

    CN107954630A

  • Water resistant coating for magnesia cement and preparation method of water resistant coating

    CN108840611A

  • Aerated concrete produced from solid waste and production method thereof

    CN118344175A